2022
DOI: 10.3389/fpubh.2022.959319
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance and role of coinfections with respiratory pathogens among individuals with confirmed severe acute respiratory syndrome coronavirus-2 infection

Abstract: IntroductionThis study aimed to determine the prevalence, viral profile, and clinical features of coinfections with severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) and other respiratory viruses.MethodsNasopharyngeal samples and clinical data of 221 hospitalized patients and 21 outpatients were collected and analyzed. Real-time reverse transcription-polymerase chain reaction was used to detect SARS-CoV-2, influenza virus, respiratory syncytial virus (RSV), human metapneumovirus (HMPV), parainfluenz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…This corresponds to rates of co-infections of 0.7% for SARS-CoV-2, of 2.4% for influenza A and of 3.7% for RSV with either of the two other viruses. Therefore, the rate of co-infections of individuals with detectable SARS-CoV-2 was lower at our center than the rates of co-infections of 7.2% reported in patients <18 years of age in a pediatric ED in Lithuania [ 55 ] and of 9.9% observed in two tertiary centers in Bulgaria [ 56 ]. We assume that the low rate of co-infections detected in our ED is related to the fact that our study cohort only included patients ≥18 years of age, and that in Austria, some containment measures were still in place at the end of 2022 ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 58%
“…This corresponds to rates of co-infections of 0.7% for SARS-CoV-2, of 2.4% for influenza A and of 3.7% for RSV with either of the two other viruses. Therefore, the rate of co-infections of individuals with detectable SARS-CoV-2 was lower at our center than the rates of co-infections of 7.2% reported in patients <18 years of age in a pediatric ED in Lithuania [ 55 ] and of 9.9% observed in two tertiary centers in Bulgaria [ 56 ]. We assume that the low rate of co-infections detected in our ED is related to the fact that our study cohort only included patients ≥18 years of age, and that in Austria, some containment measures were still in place at the end of 2022 ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 58%
“…We observed a longer duration of hospital treatment in patients co-infected with HCoV compared with those mono-infected with SARS-CoV-2. Another study of ours reported a longer hospital stay in the remaining mixed infections of SARS-CoV-2 with other respiratory viruses, as along with a greater percentage of intensive treatments [ 23 ]. A similar trend has been reported in other studies [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The weak circulation of these viruses during the COVID-19 pandemic resulted in a reduced number of co-infections, including that of SARS-CoV-2 [ 21 , 22 ]. In a previous study conducted by us, it was reported that individuals who were infected with both SARS-CoV-2 and another respiratory virus had a more severe clinical course and required more frequent hospitalisation or invasive treatment [ 23 ]. Other studies have also reported a more severe clinical picture in patients with COVID-19 who were co-infected [ [24] , [25] , [26] ].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we confirmed that white blood cells and C-reactive protein significantly mediated the relationship between the burden of comorbidity and Ct values by 29.56% and 18.13% of the total effect size, respectively. These results were unsurprising as agerelated diseases share inflammatory pathogenesis and age-related decline and dysregulation of immune function (34)(35)(36). Also, the degree of immune dysfunction correlates with disease severity (37,38).…”
Section: Discussionmentioning
confidence: 99%